Isolasi dan Karakterisasi Bakteri Asam Laktat dari Fermentasi Tape Ketan yang Beredar di Pasar Citra Niaga Jombang - Rahmah Cahya Ningrum; Nurul ‘Aini; Ana Mariatul Khiftiyah (AGROSAINTIFIKA, 2023)
Lactic Acid Bacteria (LAB) are bacteria that are widely found in traditional fermented products from Indonesia. Processed Indonesian products containing LAB are made by involving the process of fermenting foodstuffs with starch-based ingredients such as glutinous tape. Processed tape made from glutinous rice fermented by yeast. This study aims to determine the number of isolates contained in fermented sticky rice and find out how the characteristics of LAB isolates in fermented sticky rice are circulating in Citra Niaga Market, Jombang. This research is expected to be the basis for further research to determine the potential of LAB and diversity in glutinous tape. In this study, BAL was isolated from 3 brands of sticky tape circulating in the Legi Jombang Market using the isolation method with a multilevel dilution technique and showed a different number of microbes in each sample. In sample 1 there were 1.7 × 106 CFU/ml, in sample 2 there were 3.0 × 107 CFU/ml while in sample 3 there were microbes with a total of 1.14 × 105 CFU/ml. In this study it was suspected that the isolates obtained belonged to the genus Streptococcus.